TATTOOS AS ARTISTIC HERITAGE OF SOCIETY: HISTORY AND PRESENT - Burchak, Ihor; Vorobchuk, Maria; Puz, Artem (Theory and practice of design, 2023)
Today, tattoos remain a visual language of the skin, through which culture is preserved in a specific way. The article considers tattoo designs as an expression of human culture based on the system of knowledge transmission to the next generations. Systematization of the evolution of tattoos was carried out, based on which the areas of use of tattoo designs in design were analyzed and their functional features were determined. The structure of the artistic communication of tattoo designs was also investigated. Purpose. To reveal the peculiarities of the emergence and development of tattoo designs, to determine the areas of their application in design, to investigate the functional features and to determine the structure of artistic communication of tattoo designs. Methodology. Analytical, sociocultural, structural approaches, as well as theoretical research methods are applied. Results. An analysis of literary sources on the topic of the study was carried out, and on the basis of this, the evolution of tattoo designs was systematized and described. The functional properties of design that are inherent in tattoos have been studied and the areas of use of tattoo images in various fields of design have been identified. The structure of artistic communication of tattoo-drawings is determined and it is established that they are a promising component of design that allows the artist’s creative idea to be realized. Scientific novelty. For the first time, the structure of artistic communication of tattoo designs was developed, their functional features were revealed, and the use of tattoo designs not only in graphic design, but also in other areas of design was investigated. Practical significance. The results of the research can be used for further study of tattoo designs, their application in design, as well as serve as theoretical and practical material for the training of design specialists and for writing scientific papers.